The design of the Inpatient Care Monitoring and Evaluation System for the Executive Report at X Hospital - Sri Jumiati Agustina; Kemal Nazaruddin Siregar (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
One of the information systems needed in a hospital to support services is the inpatient information system. Several field constraints that often occur and can impede patient services include: limited bed space, hindered coordination between units or rooms, sudden changes in bed space requirements, the lack of integration of information systems, incomplete and inaccurate documentation of patient mobilization, the length of the patient discharge process, unavailable facilities in rooms, and the existence of hospital service indicators that must be achieved. Based on the above, a real-time and integrated information system is required, starting from the registration of inpatients to their discharge, in order to improve the quality of service and patient satisfaction. The design of the Inpatient Monitoring and Evaluation System for the Executive Report is an enhancement of the hospital information system that integrates all inpatient patient service activities, including supporting facilities, to generate useful information for monitoring and developing inpatient care services. This information can be used as a basis for decision-making by the leaders. The design of the Inpatient Monitoring and Evaluation System for the Executive Report utilizes the Systems Development Life Cycle (SDLC) method in the form of a prototype, with the drafting phase starting from design to development. The final result of this information system design consists of comprehensive, integrated, and real-time information related to patient activities from admission to discharge, presented in a dashboard that is useful for monitoring and evaluating inpatient care services. It can also serve as a basis for decision-making by hospital leaders and achieving hospital indicators. Keywords: Bed management, dashboard, information, inpatient, integration